Synthesis and thermal characterization of tri-substituted triazines - Baykal, Duygu. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Cyanuric chloride has huge application areas in chemical industries on drug, agriculture, polymer, dye and leather because of fact that cyanuric chloride is commercially cheap. In addition to this, its substitution reaction can be controlled easily via temperature. The most variety of application is in polymer industry. One of the applications of cyanuric chloride is polymerization of substituted s-triazines via a monomer with a nucleophilic group or end capping. In this study tri-substituted triazines were synthesized starting from cyanuric chloride and their thermal behavior were investigated in the presence of different nucleophiles to predict their potential for polymerization through trans-esterification reactions.
Keywords: Triazines.